Geometrical Techniques for Electric Field Control in (Ultra) Wide Bandgap Power Electronics Modules - Ghessemi, Mona (Electrical Insulation Conference and Electrical Manufacturing Expo, 2018)
Regarding the outstanding properties, commercial availability of starting material, and maturity of the technological processes, silicon carbide (SiC) and gallium nitride (GaN) with a relatively large bandgap of 3.3 eV and 3.4 eV, respectively are the more promising semiconductor materials known as wide bandgap (WBG) semiconductors. WBG semiconductors which are expected to have better efficiency, higher temperature tolerance, and higher voltage blocking capability than their silicon (Si) counterparts having a bandgap of 1.1 eV are changing the landscape of power electronics industry. Moreover, a new class of semiconductor materials so-called ultrawide-bandgap (UWBG) semiconductors with bandgaps higher than that of GaN including diamond (C), gallium oxide (Ga2O3), and aluminum nitride (AIN) currently investigated will be generation-after-next power electronics. However new packaging technologies are needed to realize the mentioned superior system performance with WBG and UWBG devices. Among various factors needed to be addressed for high-density packaging designs of high voltage WBG and UWBG devices, the high electric fields, especially at the edges of the substrate metallization, can lead to unacceptable levels of partial discharges in the silicone gel commonly used as encapsulations. In this paper, geometrical techniques for electric field control inside (U)WBG power electronics modules are studied by finite element method models (FEM) developed in COMSOL Multiphysics.